Illustrated dictionary of architecture - Burden, Ernest E., 1934- 4 0 16; 5 (New York : McGraw-Hill, 2012)
Contains 8,000 alphabetically arranged entries that focus on architectural style, building types, design, composition, materials, parts, elements, and form.
Keywords: 2 -- 0; 6; Architecture -- 20 -- Dictionaries; 20; 2